Imaging stem cell distribution, growth, migration, and differentiation in 3‐D scaffolds for bone tissue engineering using mesoscopic fluorescence tomography. Issue 1 (22nd November 2017) - Tang, Qinggong; Piard, Charlotte; Lin, Jonathan; Nan, Kai; Guo, Ting; Caccamese, John; Fisher, John; Chen, Yu
Abstract: Regenerative medicine has emerged as an important discipline that aims to repair injury or replace damaged tissues or organs by introducing living cells or functioning tissues. Successful regenerative medicine strategies will likely depend upon a simultaneous optimization strategy for the design of biomaterials, cell‐seeding methods, cell‐biomaterial interactions, and molecular signaling within the engineered tissues. It remains a challenge to image three‐dimensional (3‐D) structures and functions of the cell‐seeded scaffold in mesoscopic scale (>2 ∼ 3 mm). In this study, we utilized angled fluorescence laminar optical tomography (aFLOT), which allows depth‐resolved molecular characterization of engineered tissues in 3‐D to investigate cell viability, migration, and bone mineralization within bone tissue engineering scaffolds in situ. Abstract : The authors utilized angled fluorescence laminar optical tomography (aFLOT), which allows depth‐resolved molecular characterization of engineered tissues in 3D to investigate cell viability, migration, and bone mineralization within bone tissue engineering scaffolds in situ.